“Planetary Linguistic Personality” Category and Bi/Polylinguistic Modeling of the Pedagogical Process of Higher School Professional Training: Sochi Linguistic and Rhetorical School - Vorozhbitova, A.A.; Marchenko, O.I.; Timofeyev, A.V.; Issina, G. I. (Academic Publishing House Researcher s.r.o., 2018)
The article substantiates the synergistic concept of complex linguistic and rhetorical (L&R) training necessary for the high-quality professional training of a future specialist of any direction and profile of higher school education; the specification is made on the example of a teacher of a foreign language (foreign languages). The restructuring of the educational process in the framework of the bi/polylinguistic learning model developed by representatives of the Sochi L&R School is based on the positions set out in the article. For the development of a professional bi/polylinguistic personality of a future specialist, more effective than the specialized formation of the L&R competence only in the field of foreign languages is the purposeful and coordinated work of the entire teaching staff in the framework of “the single linguistic-rhetorical and cultural-speech regime” according to the formation of Russian and foreign language L&R competencies of learners. The speech-thinking culture of future specialists, integrating in a bi/polylinguistic relation, including an invariant core and ethno-linguistic- rhetorical variants, is a qualitatively new psycholinguistic formation, which is formed on the basis of the interaction of the substructures of the primary and secondary linguistic personality. A necessary condition for the formation of speech-thinking culture of future specialists is the formation of students' readiness for professional self-designing as a future specialist on the basis of a bi/polylinguistic L&R competence of mixed type.